PELAKSANAAN UNIT PRODUKSI PADA PROGRAM STUDI KEAHLIAN JASA BOGA DI SMK NEGERI 9 PADANG - Maria S, Krista; Baidar, Baidar; Elida, Elida (Journal of Home Economics and Tourism, 2013)
This research is motivated by student complaints regarding the implementation of the production unit at the Skills Program at SMK Padang 9, which in practice did not involve students, so that the production unit functions as a forum to train students to be neglected. The purpose of this study was (1) to describe the types of activities in production unit Catering SMK Padang 9, (2) to describe the production unit processing equipment Catering at SMK Padang 9 and (3) to describe the benefits of the production unit at SMK Negeri 9 field. This research is a qualitative descriptive study. The data of this research is the implementation of the production unit at the Hospitality Skills Program at SMK Padang 9. Data was collected using interviews, observations, and questionnaires. In the informants, namely: guidance counselor production unit (2 people), students involved in the production unit (8). On the implementation of the type of activities production unit also works with outside parties such as cooperation with the agency in terms of catering orders. 2) Processing equipment production unit is complete, most of the equipment used in the production units are not neatly arranged. 3) Benefits of the production unit as a place of learning for students, helping funding for maintenance, additional facilities. . Â  Keywords: Production Units, Catering Services, SMK Padang 9